Title page: psychometric properties of literacy of suicide scale (LOSS) in iranian population: long form - Alireza Jafari; Mahdi Moshki; Ali Mohammad Mokhtari; Amirarsalan Ghaffari; Mahbobeh Nejatian (BMC, 2023)
Abstract Introduction Suicide and suicide attempts are among the most important indicators of mental health in the world. In this research, the validity and reliability of Literacy of Suicide Scale (LOSS) was examined in general people over the age of 18. Methods This cross-sectional psychometric study was conducted in 2022 among 952 general population in Iran. Participants were selected by two methods of proportional stratified sampling and simple random sampling. The internal consistency of the tools was assessed using Cronbach's alpha coefficient, and McDonald omega coefficient. Also, test-retest reliability was checked by Intraclass Correlation Coefficient (ICC). Results In the confirmatory factor analysis section, the factor loading of all questions were above 0.4 and one questions were deleted and final model with four factors and 25 questions was confirmed (Some of goodness-of-fit indexes: AGFI = 0.910, RMSEA = 0.050, IFI = 0.901, and χ2/df = 3.333). For all questions, the Cronbach's alpha coefficient was 0.859, McDonald omega coefficient was 0.866, and ICC was 0.895. Finally, the Persian long version of LOSS was approved with 25 items and four subscales: causes/triggers (9 items), risk factors (7 items), signs and symptoms (5 items) and treatment/prevention (4 items). Conclusion The Persian long version of LOSS with four subscales and 25 items is an appropriate tool to investigate the state of suicide literacy in the public population.